2015
DOI: 10.2147/tacg.s68635
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary capillary hemangiomatosis: a focus on the EIF2AK4 mutation in onset and pathogenesis

Abstract: Pulmonary capillary hemangiomatosis (PCH) is a pulmonary vascular disease that mainly affects small capillaries in the lung, and is often misdiagnosed as pulmonary arterial hypertension or pulmonary veno-occlusive disease due to similarities in their clinical presentations, prognosis, and management. In patients who are symptomatic, there is a high mortality rate with median survival of 3 years after diagnosis. Both idiopathic and familial PCH cases are being reported, indicating there is genetic component in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…However, there was no evidence of PVOD in this cat. In humans, mutations in the EIF2AK4 gene are a risk factor in the development of PCH [ 14 ]. Future studies investigating the aforementioned EIF2AK4 gene mutation are needed to establish this association in dogs and cats with PCH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no evidence of PVOD in this cat. In humans, mutations in the EIF2AK4 gene are a risk factor in the development of PCH [ 14 ]. Future studies investigating the aforementioned EIF2AK4 gene mutation are needed to establish this association in dogs and cats with PCH.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, PCH has been described in association with aortic stenosis [ 6 ], Kartagener syndrome [ 7 ], systemic lupus erythematous [ 8 ], scleroderma [ 9 ], Takayasu’s arteritis [ 10 ], hypertrophic cardiomyopathy [ 11 ] and neoplasia [ 12 , 13 ]. Mutations in the eukaryotic translation initiation factor 2 alpha kinase 4 (EIF2AK4) gene are a risk factor in the development of PCH [ 14 ]. It has also been proposed that PCH is not a separate disease, but rather represents a secondary angioproliferative response to pulmonary venous hypertension as seen in PVOD [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…EIF2AK4 gene mutation has been confirmed in pulmonary vein occlusive disease (PVOD) and pulmonary capillary hemangioma (PCH) (45,46), but there are no relevant studies confirming its pathogenesis and prognostic roles in liver cancer. Huang et al (47) also confirmed through similar studies that CNOT6, UPF3B, MRPL54, IFIT5 and PPARGC1A are the key RBP coding genes for primary HCC and can also predict the survival of patients.…”
Section: Verification Of the Expression Level In The Hpa Databasementioning
confidence: 99%
“…Pulmonary veno-occlusive hypertension is allelic at the PPH1 locus ( BMPR2 ), while the recessive form is caused by mutations in EIF2AK4. 42 Finally, Group 5 PH includes a variety of acquired and heritable diseases such as the AD lymphangioleiomyomatosis 43 and lysosomal storage diseases such as glycogen storage disease types 1 and 3 44 , 45 and Gaucher disease type 1 46 , 47 . Clinical genetics with counselling and pedigree construction, search for known risk factors and annotation of novel potential risk factors, family investigation, and genetic testing are currently being translated in the clinical setting.…”
Section: Major Genetic Cardiovascular Diseasesmentioning
confidence: 99%